What does the holy Koran say about Christianity and Judasim = Qu’est-ce que dit le Coran sur le Christianisme et le Judaisme = Was sagt der Koran uber das Christentum und das Judentum = Kuran-ı Kerim Hristiyanlık ve Yahudilik hakkında ne diyor? (Ankara)
193 s.